Childhood malnutrition and maltreatment are linked with personality disorder symptoms in adulthood: Results from a Barbados lifespan cohort. (November 2018) - Hock, Rebecca S.; Bryce, Cyralene P.; Fischer, Laura; First, Michael B.; Fitzmaurice, Garrett M.; Costa, Paul T.; Galler, Janina R.
Highlights: Early childhood adversities are linked with PD symptoms in adulthood. Malnutrition is linked with paranoid, schizoid, avoidant, and dependent PDs. Maltreatment is linked with paranoid, schizoid, avoidant, and schizotypal PDs. Overall, those exposed to both adversities had even higher PD scores. Interventions should focus on immediate and long-term outcomes. Abstract: Both childhood malnutrition and maltreatment are associated with mental health problems that can persist into adulthood. Previously we reported that in Barbados, those with a history of infant malnutrition were more likely to report having experienced childhood maltreatment. Few studies, however, address the long-term outcomes of those who have been exposed to both. We assessed the unique and combined associations of a history of early malnutrition and childhood maltreatment with personality pathology in mid-adulthood in participants of the 47-year longitudinal Barbados Nutrition Study. We used the Structured Clinical Interview for DSM-IV-TR Axis II Personality Disorders Personality Questionnaire (SCID-II-PQ) and NEO Personality Inventory-Revised derived Five-Factor Model (NEO PI-R FFM) personality disorder (PD) scores to assess personality pathology, the Childhood Trauma Questionnaire-Short Form (CTQ-SF) to assess childhood maltreatment, and clinical documentation of malnutrition in infancy. We tested the associations of malnutrition and maltreatment with PD scores using linear regression models, unadjusted and adjusted for other childhood adversities. We found increased scores for paranoid, schizoid, avoidant, and dependent PDs among those who had been malnourished and increased scores for paranoid, schizoid, schizotypal, and avoidant PDs among those with higher childhood maltreatment scores. Overall, those exposed to both adversities had even greater PD scores.